Scale effects on span elongation beneath pipelines and cables in live-bed conditions - Bingchang Zhang; Hongwei An; Scott Draper; Xu Zhao; Hongyi Jiang; Phil Watson; Liang Cheng (Coastal Engineering, 2026)

Hazardous harbor hydrodynamic response to extreme transoceanic swell events - Lidian Guo; Zhenjun Zheng; Xiaozhou Ma; Mingfu Tang; Guohai Dong; Hongwei An; Scott Draper (Natural Hazards, 2026)

A review of measured rogue waves: Spatio-temporal characteristics, occurrence probability, physical mechanisms, and predictability - Ruili Fu; Huayi Cai; Guohai Dong; Gang Wang; Aifeng Tao; Jinhai Zheng; Mingfu Tang; Hongwei An; Scott Draper; Xiaochen Li (Ocean Engineering, 2026)

Scour mitigation for squat, shallowly embedded structures - Lili Qu; Scott Draper; Hongwei An; Phil Watson (Coastal Engineering, 2026)

IDDES simulation of side-by-side cylinder flow with different turbulence intensities at subcritical Reynolds number - Zhiqiang Liu; Guohai Dong; Xiaozhou Ma; Mingfu Tang; Hongwei An; Scott Draper (Ocean Engineering, 2026)

An experimental investigation of local scour at squat, shallowly embedded subsea structures - Lili Qu; Hongwei An; Scott Draper; Phil Watson; Liang Cheng (Coastal Engineering, 2025)

Hydrodynamic forces on small-diameter pipelines in combined wave-and-current flows - Yunfei Teng; Terry Griffiths; Hongwei An; Scott Draper; Liang Cheng; Henning Mohr; Cheng Zhang; Guoqiang Tang; Lin Lu (Coastal Engineering, 2025)

Influence of bed ripples on scour-induced span elongation of pipelines/cables - Bingchang Zhang; Scott Draper; Hongwei An; Hongyi Jiang; Liang Cheng (Coastal Engineering, 2025)

Laboratory validation of the extended SWASH model for modeling wave dynamics under depth-uniform ambient currents - Lidian Guo; Zhenjun Zheng; Xiaozhou Ma; Mingfu Tang; Guohai Dong; Hongwei An; Scott Draper (Ocean Modelling, 2025)

Effect of steady boundary-layer flow on the hydrodynamic forces on a near-wall cylinder in currents - Yunfei Teng; Terry Griffiths; Liang Cheng; Yan Qu; Hongwei An; Scott Draper; Zhe Gao; Guoqiang Tang; Lin Lu (Ocean Engineering, 2024)

Potential of repurposing decommissioned subsea flowlines to dynamically installed anchors - Muhammad Shazzad Hossain; Ming Hui Gao; Yuxia Hu; Scott Draper (Ocean Engineering, 2024)

A review of scour impacting monopiles for offshore wind - Lili Qu; Hongwei An; Scott Draper; Phil Watson; Ming Zhao; John Harris; Richard Whitehouse; Di Zhang (Ocean Engineering, 2024)

Non-linear vibration of free spanning subsea pipelines with multi-dimensional mid-plane stretching - Ali Karrech; Maryam Abdolahpour; Hongwei An; Fraser Bransby; Scott Draper; Zhechen Hou; Phil Watson (Engineering Structures, 2024)

On the application of overset meshing to numerical studies of roll damping of hulls in complex scenarios - Kemeng Xi; Ian A. Milne; Scott Draper; Lifen Chen (Ocean Engineering, 2023)

The offshore renewables industry may be better served by new bespoke design guidelines than by automatic adoption of recommended practices developed for oil and gas infrastructure: A recommendation illustrated by subsea cable design - Terry Griffiths; Scott Draper; Liang Cheng; Hongwei An; Marie-Lise Schläppy; Antonino Fogliani; David White; Stuart Noble; Daniel Coles; Fraser Johnson; Bryan Thurstan; Yunfei Teng (Frontiers in Marine Science, 2023)
Introduction There is an emerging need for the offshore renewable industry to have their own bespoke design guidelines because the associated projects and offshore facilities differ in fundamental ways to oil and gas facilities. Offshore renewable energy (ORE) facilities have already surpassed the numbers of installed facilities in the oil and gas industry by an order of magnitude and demand is forecast to continue growing exponentially. In addition ORE facilities often have different response characteristics and limit states or failure modes as well as profoundly different risk and consequence profiles given they are generally uncrewed and do not contain explosive hydrocarbon fluids which might be released into the environment. Therefore, the purpose of this paper is to advocate for licensing bodies and regulators (such as the various national PEL 114 committees) to challenge the process of automatic adoption of oil and gas design processes, while pushing for offshore renewables to be treated differently, when appropriate, with more relevant and applicable guidance. Methods To support this argument we present new bespoke design guidance developed for subsea cables based on specific modes of cable behaviour, which often differ from pipelines. We also show worked examples from recent project experience. The results from on-bottom stability analyses of a set of cables are compared between conventional oil and gas guidance following DNV-RP-F109 versus the stability using cable-optimised approaches. Results The outcomes from the ‘conventional’ oil and gas results are not simply biased compared to cable-optimised design methods, with a trend of being either conservative or unconservative. Instead, the results of the two methods are very poorly correlated. This shows that the oil and gas approach isn't simply biased when applied to cables, but is instead unreliable because it doesn't capture the underlying failure conditions. These analytical comparisons are supported by field observation - the ocean doesn't lie, and makes short work of any anthropogenic structures which are designed with inadequate appreciation of the real world conditions. Discussion To support the rapid growth of ORE, we should therefore actively pursue opportunities to rewrite the design rules and standards, so that they better support the specific requirements of ORE infrastructure, rather than legacy oil and gas structures. With more appropriate design practices, we can accelerate the roll out of ORE to meet net zero, and mitigate the climate crisis.

A Method for Measuring Hydrodynamic Force Coefficients Applied to an Articulated Concrete Mattress - Hongwei An; Xiaoyuan Hu; Scott Draper; Liang Cheng; Binsar Lubis; Mehrdad Kimiaei (Journal of Marine Science and Engineering, 2022)
A physical model testing method to determine the hydrodynamic force coefficients of an object is proposed and applied to an articulated concrete mattress placed on a flat surface under steady current condition. The test setup, which comprises of a pulley system that is able to pull the concrete mattress in either direction relative to the flow (e.g., with the flow direction or against the flow direction) and one load cell to measure the force required to pull the mattress, is simple and straightforward. Writing the equations of load balance for two different pulling directions allows the force coefficients to be deduced. The novelty and advantages of the method are that it completely removes the difficulties associated with measuring forces on individual concrete blocks and isolating the mattresses from contacting the solid surface, which were common in conventional test methods for measuring hydrodynamic forces on structures founded on a solid surface. A series of flume tests have been conducted to demonstrate the validity of the proposed method. It is expected that the proposed testing method is applicable to a wide range of structures, bed surfaces and flow conditions.

International consensus principles for ethical wildlife control - Sara Dubois; Nicole Fenwick; Erin A. Ryan; Liv Baker; Sandra E. Baker; Ngaio J. Beausoleil; Scott Carter; Barbara Cartwright; Federico Costa; Chris Draper; John Griffin; Adam Grogan; et al. (Conservation Biology, 2017)
Human–wildlife conflicts are commonly addressed by excluding, relocating, or lethally controlling animals with the goal of preserving public health and safety, protecting property, or conserving other valued wildlife. However, declining wildlife populations, a lack of efficacy of control methods in achieving desired outcomes, and changes in how people value animals have triggered widespread acknowledgment of the need for ethical and evidence‐based approaches to managing such conflicts. We explored international perspectives on and experiences with human–wildlife conflicts to develop principles for ethical wildlife control. A diverse panel of 20 experts convened at a 2‐day workshop and developed the principles through a facilitated engagement process and discussion. They determined that efforts to control wildlife should begin wherever possible by altering the human practices that cause human–wildlife conflict and by developing a culture of coexistence; be justified by evidence that significant harms are being caused to people, property, livelihoods, ecosystems, and/or other animals; have measurable outcome‐based objectives that are clear, achievable, monitored, and adaptive; predictably minimize animal welfare harms to the fewest number of animals; be informed by community values as well as scientific, technical, and practical information; be integrated into plans for systematic long‐term management; and be based on the specifics of the situation rather than negative labels (pest, overabundant) applied to the target species. We recommend that these principles guide development of international, national, and local standards and control decisions and implementation.